1983
DOI: 10.1021/ac00253a023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polyaromatic hydrocarbon mixtures with laser ionization gas chromatography/mass spectrometry

Abstract: the U.S. Environmental Protection Agency under 1A6-EPA-80-D-X0958 is gratefully acknowleged. This work is taken in part from a dissertation to be submitted to the Graduate School, University of Maryland, by W. J. Sonnefeld in partial fulfillment of the requirement for the Ph.D. degree in chemistry. Certain commercial equipment, instruments, or materials are identified in this paper to specify adequately the experimental procedure. Such identification does not imply recommendation or endorsement by the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…The LODs obtained in this study are similar to those reported by Rhodes et al: the LODs of 7 PAHs obtained using a nanosecond laser (10 ns) are in the range of 0.2 -5.0 pg. 26 It is noted that Hauler et al have obtained a LOD of 80 ppt for NAP with on-line measurements and LODs in the 100 pg range for PHE, CHR, and some other PAHs using a laser desorption technique. 27 …”
Section: Standard Samplementioning
confidence: 99%
“…The LODs obtained in this study are similar to those reported by Rhodes et al: the LODs of 7 PAHs obtained using a nanosecond laser (10 ns) are in the range of 0.2 -5.0 pg. 26 It is noted that Hauler et al have obtained a LOD of 80 ppt for NAP with on-line measurements and LODs in the 100 pg range for PHE, CHR, and some other PAHs using a laser desorption technique. 27 …”
Section: Standard Samplementioning
confidence: 99%
“…GC-MPI-MS. Multiphoton ionization is well suited for complex mixture analysis particularly when coupled with gas chromatography, as has been demonstrated by using TOF mass spectrometry (43). More recently, MPI has been coupled with the pulsed GC introduction for FTMS high-resolution targeted compound analysis (44).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Laser ionization utilizes the resonanceenhanced multi-photon ionization (REMPI) method, which features molecular selectivity and enables fragment-free ionization. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The authors of the present report have developed an online monitoring method using ultrasonic jet-type laser ionization TOFMS (time of flight mass spectrometry), and have confirmed the usefulness of this method with respect to PCBs. 8 Because an extremely large number of molecules exist in environmental gas, the requirement is for a method that is for relatively large molecular selectivity in a short time, so as to enable the rapid analysis of trace concentrations.…”
Section: Introductionmentioning
confidence: 74%